2017
DOI: 10.1177/2324709617741144
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Escherichia coli Hemolytic Uremic Syndrome in a 10-Year-Old Male With Severe Neurologic Involvement Successfully Treated With Eculizumab

Abstract: Hemolytic uremic syndrome (HUS) can be classified as typical and atypical, and the treatment recommendations currently differ between the 2 types. Eculizumab is recommended as first-line treatment for atypical HUS; however, its use in typical HUS has been controversial. We report a case of a 10-year-old male with severe neurologic impairment who was successfully treated with eculizumab, which was started 4 days after onset of neurologic symptoms. Our case supports the use of eculizumab in typical HUS with neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The treatment of acquired or congenital thrombocytopenia with Eculizumab, an anti-C5 monoclonal antibody which blocks complement activation, has proven successful (Pecoraro et al, 2015;Bitzan et al, 2018). Since VT can activate complement, this approach has been tested for efficacy in eHUS (Rasa et al, 2017;Walsh and Johnson, 2019). Therapeutic effect has been shown, particularly for patients with neurological symptoms (Percheron et al, 2018) but results overall are, as yet, highly variable (Loos et al, 2018;Monet-Didailler et al, 2019).…”
Section: New Therapeutics Complementmentioning
confidence: 99%
“…The treatment of acquired or congenital thrombocytopenia with Eculizumab, an anti-C5 monoclonal antibody which blocks complement activation, has proven successful (Pecoraro et al, 2015;Bitzan et al, 2018). Since VT can activate complement, this approach has been tested for efficacy in eHUS (Rasa et al, 2017;Walsh and Johnson, 2019). Therapeutic effect has been shown, particularly for patients with neurological symptoms (Percheron et al, 2018) but results overall are, as yet, highly variable (Loos et al, 2018;Monet-Didailler et al, 2019).…”
Section: New Therapeutics Complementmentioning
confidence: 99%
“…We identified eight case series and case reports that described 21 total patients with STEC‐HUS treated with eculizumab . It included the case series study published by Lapeyraque et al who first systematically described the use of eculizumab in three pediatric cases of severe STEC‐HUS with neurological involvement, demonstrating rapid neurologic improvement within 24 h of first dose, and the normalization of disease markers including platelet count and LDH .…”
Section: Resultsmentioning
confidence: 99%
“…The potential benefit of eculizumab in STEC-HUS has not been established to date and remains a matter of debate and ongoing research. Based on the dramatic effectiveness of eculizumab in atypical HUS, and on evidence showing complement activation during STEC-HUS, complement blockade has been attempted and reported in some cases and small series [8][9][10][11]. In a first report including 3 young patients with severe STEC-HUS (i.e., neurological involvement), administration of eculizumab was rapidly followed by a dramatic resolution of symptoms, suggesting potential benefit of therapeutic complement blockade [8].…”
Section: Case Reports In Nephrology and Dialysismentioning
confidence: 99%
“…Despite the higher risk of death associated with severe CNS involvement in STEC-HUS, the appropriate treatment remains ill-defined. Experimental data showed that Shiga toxin directly activates complement system and case series suggested that complement inhibition with eculizumab may be beneficial in patients with STEC-HUS complicated by CNS involvement [7][8][9][10][11]. However, such benefit was not confirmed among patients treated during the 2011 outbreak of E. coli O104:H4 and whether eculizumab should be used in patients with STEC-HUS and severe CNS symptoms still remains debated [12].…”
Section: Introductionmentioning
confidence: 99%